High gain couple feed multiband wearable antenna for 5G and sub‐6 GHz communications. Issue 12 (18th October 2022) - Saeidi, Tale; Karamzadeh, Saeid
Abstract: A multi‐band, small, high gain, low specific absorption rate (SAR), and circularly polarized (CP) textile wearable antenna fed using aperture coupled technique is designed on two layers of denim ( ε r = 1.2, h  = 0.787 mm as feeding layer) and felt ( ε r = 1.3, h  = 1.5 mm as a resonating layer) textile substrates. The antenna is designed on two layers with two relative permittivities to enhance the BW and reduce the negative mutual coupling. Afterward, another layer of denim with the complete ground of ShieldIt conductor is added to decrease the SAR value along with the directive gain. The antenna works for Industrial, Scientific, and Medical (ISM), 5G, and sub‐6 GHz communication systems as it operates at 2.45–2.55 GHz and 3.8 GHz (3.6–4.15 GHz), and 5.6 GHz (5.55–5.65 GHz), respectively. The proposed antenna has the maximum directive gain of 8.35 dBi, acceptable SAR values at a 10 mm distance from the human body for both standards. In addition, the antenna's CP is examined, showing AR values of <2.5 dB at the working BW. Finally, the proposed antenna is measured and compared with the simulation results. A good agreement exists between simulation and measurement results.